The monochrome LCD Driver Design and Implementation Based on Framebuffer - Li Zhi-hui; Xian Jinlong (Institute of Advanced Engineering and Science, 2013)
Recently, the LCD applications have developed very rapidly, especially the application of the monochrome LCD in certain areas. This paper, on hardware, introduced the connection between monochrome LCD HEM160160-07C2 and ARM9-based AT91SAM9261; on software, respectively introduced monochrome LCD driver implementation based on GPIO and based on Framebuffer. By the two mode analysis, the mode based on Framebuffer is better, ultimately has been validated in the project experiment. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.2868